Application of the Subequation Method to Some Differential Equations of Time-Fractional Order - Bekir, Ahmet; Aksoy, Esin (ASME, 2015)
The main goal of this paper is to develop subequation method for solving nonlinear evolution equations of time-fractional order. We use the subequation method to calculate the exact solutions of the time-fractional Burgers, Sharma-Tasso-Olver, and Fisher's equations. Consequently, we establish some new exact solutions for these equations.
Keywords: exact solution; subequation method; fractional differential equation; fractional complex transformation; fractional calculus; Engineering; Mechanics